Critical Perspectives on Public Systems Management in India - Through the Lens of District Administration - Ghalke, Avinash (Prabandhan: Indian Journal of Management, 2021)
The book - Critical Perspectives on Public Systems Management in India - Through the Lens of District Administration provides an overview of India’s public administration system by studying the district administration. Using a two-year project that involved conferences, interviews, and shadowing district collectors, the authors described the obstacles that a district collector faces in his/her day-to-day operations. The book is a must-read for any candidate aspiring to be a public service officer.